Gay and Lesbian Identity Negotiation in Family - Yuri Dwi Yudhistira; Dr. Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Homosexual is a phenomenon in society defined as deviant sexual orientation. So as to live a life in society requires recognition of people around, especially in the family as the first step in the process of identity formation before to the community. This study is a qualitative research, the paradigm used is critical constructivist paradigm where the research focus is homosexual identity negotiations on family. The theory used is the theory of inter-personal communication in the family Julia T. Wood, theory of social construction and negotiation Charles R. Ngangi, and theory queer identity Stella Ting-Toomey. While phenomenology is used as an approach to data analysis for research based on phenomena that occur in the negotiation of identity in the family. The results showed that the process of negotiation within the family made through three stages, the first is the identification of self through self-awareness, knowledge, and personal experience. Secondly, the negotiations in the community with the stage through close friends first and continuing to the public openly. Third, the negotiations in the family that resulted in two decisions of acceptance is due to family relationship status as parent-child factor or rejection that has two consequences which gives the opportunity to change or leave the family. Acceptance or rejection of the identity negotiation process also influenced by the type of family that is traditional, independent, separate. The type based on the familiarity of family members relationship, resolve conflicts, and the interests of family members. Through the construction theory found that the appearance is very influential on the rejection or acceptance of gay and lesbian identity that has been adapted to the men and women gender roles. Disclosure of identity as a gay and lesbian to family is key success in the identity negotiation that considered inappropriate to what happened in the community. The results found that interpersonal communication in the family determines the acceptance or rejection of negotiations based on the type of family.